Left ureteral tumor five years after radical cystectomy associated with duplication of inferior vena cava a case report - Inaba, Y (Hinyokika kiyo. Acta urologica Japonica, 1989)
A 70-year-old male was admitted with left lumbago. He underwent a radical cystectomy five years earlier due to recurrent bladder carcinoma. Excretory urography revealed left hydronephrosis, left hydroureter and a right ureteral stone. Antegrade pyelography and urinary cytology of left kidney suggested the presence of left ureteral tumor and this was confirmed by an endoscopic work up through the nephrostomy. This patient was revealed to have a duplicated inferior vena cava by CT scan and vena cavography. A radical left nephroureterectomy was done uneventfully. M-VAC was adopted for post operative therapy